T-Cells Specific for a Self-Peptide of ApoB-100 Exacerbate Aortic Atheroma in Murine Atherosclerosis - Shaw, Michael K.; Tse, Kevin Y.; Zhao, Xiaoqing; Welch, Kathryn; Eitzman, Daniel T.; Thipparthi, Raghavendar R.; Montgomery, Paul C.; Thummel, Ryan; Tse, Harley Y. (Frontiers in Immunology, 2017)
On the basis of mouse I-Ab binding motifs, two sequences of the murine apolipoprotein ApoB-100, mApoB1003501-3515 (designated P3) and mApoB-100978-992 (designated P6), were found to be immunogenic. In this report, we show that P6 is also atherogenic. Immunization of Apoe–/– mice fed a high fat diet with P6 resulted in enhanced development of aortic atheroma as compared to control mice immunized with an irrelevant peptide MOG35-55 or with complete Freund's adjuvant (CFA) alone. Adoptive transfer of lymph node cells from P6-immunized donor mice to recipients fed a high fat diet caused exacerbated aortic atheromas, correlating P6-primed cells to disease development. Finally, P6-specific T cell clones were generated and adoptive transfer of T cell clones into recipients fed a high fat diet led to significant increase in aortic plaque coverage when compared to control animals receiving a MOG35-55-specific T cell line. Recipient mice not fed a high fat diet, however, did not exhibit such enhancement, indicating that an inflammatory environment facilitated the atherogenic activity of P6-specific T cells. That P6 is identical to or cross-reacts with a naturally processed peptide of ApoB-100 is evidenced by the ability of P6 to stimulate the proliferation of T cells in the lymph node of mice primed by full length human ApoB-100. By identifying an atherogenic T cell epitope of ApoB-100 and establishing specific T cell clones, our studies open up new and hitherto unavailable avenues to study the nature of atherogenic T cells and their functions in the atherosclerotic disease process.